2022
DOI: 10.1097/ta.0000000000003799
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis comparing postoperative outcomes of laparoscopic versus open omental patch repair of perforated peptic ulcer

Abstract: BACKGROUND:The mainstay of surgical management of perforated peptic ulcer is omental patch repair. Advances in minimally invasive techniques have shown feasibility of laparoscopic omental patch repair (LOPR). Laparoscopic omental patch repair is limited by learning curve (LC), but there is a lack of reporting of LC in LOPR. This study aims to compare outcomes following LOPR versus open omental patch repair (OOPR) with reporting of LC. METHODS: PubMed, Embase, The Cochrane Library, and Scopus were systematicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 66 publications
(196 reference statements)
0
0
0
Order By: Relevance
“…Comparing miMVR as a whole vs oMVR, our study demonstrated better short-term outcomes. This is not surprising; benefits of MIS have been shown to be superior compared with open surgery in both benign and malignant conditions, such as omental patch repair for perforated peptic ulcer, oesphagectomy, colorectal resection and liver resection[ 12 - 15 ]. The concept behind the benefits of MIS remains the same regardless of the type of surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing miMVR as a whole vs oMVR, our study demonstrated better short-term outcomes. This is not surprising; benefits of MIS have been shown to be superior compared with open surgery in both benign and malignant conditions, such as omental patch repair for perforated peptic ulcer, oesphagectomy, colorectal resection and liver resection[ 12 - 15 ]. The concept behind the benefits of MIS remains the same regardless of the type of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, MVR and/or PE is a major and complex surgery with post-operative morbidity ranging from 20%-80%[ 8 ], and 30-d mortality of 0.5%-2.0%[ 9 - 11 ]. Minimally invasive surgery (MIS) which has been well-established as standard of care both benign and malignant intra-abdominal pathologies[ 12 - 15 ], may prove its utility on short-term post-operative outcomes. A retrospective study by Kazi et al [ 16 ] on 158 patients who underwent PE for LARC showed reduced intra-operative blood loss (900 vs 1600 mL, P < 0.001) and incidence of wound infections (8.2% vs 17.5%, P = 0.02) for minimally invasive PE compared with open PE, with similar 3-year overall survival (OS)[ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The simple suture technique to repair the PPU is usually recommended because of its feasibility and low procedure time (12,15,42). Pedicled omental patch repair is another favorable technique, especially in cases with a friable edge or a large perforation, which cannot allow the approximation of perforation edges (20,(48)(49)(50). Regarding postoperative management for those PPU with H. pylori infection, proton pump inhibitors and eradication of H. pylori infection are essential to reduce peptic ulcer recurrence (40,51,52).…”
Section: Discussionmentioning
confidence: 99%
“…2,3 For select cases, purely endoscopic options, such as stent placement, Over The Scope Clips (OTSC®), and Endoscopic Vacuum Therapy, are also emerging. [4][5][6][7] Yet, the postoperative management of this condition is still burdened by old traditions such as prolonged nasogastric decompression and nil per os. 8 Enhanced recovery after surgery or fast-track recovery has been used with good results in elective procedures to optimize outcomes since the 1990s.…”
Section: Introductionmentioning
confidence: 99%